'It's not about me, it's about my community': A mixed-method study of civic websites and community efficacy. (October 2016) - Cantijoch, Marta; Galandini, Silvia; Gibson, Rachel
This article examines whether the Web and particularly a new breed of civic action sites operated by non-governmental actors provide a new pathway into wider community engagement. Using an innovative mixed methodology, we conduct a qualitative and quantitative over-time analysis of the users of four civic action sites developed by mySociety, an online UK non-profit organisation. The key question posed is whether the highly targeted or 'particularised' actions that these sites promote, such as contacting a local councillor, have a spill-over effect in terms of increasing feelings of empowerment in the local community. Alternatively are they attracting and reinforcing the resource bias of the most active citizens? The results are mixed in that they confirm that users of these sites are typically more aware and engaged than average. However, it is also clear that they have integrated these tools into their existing repertoire of engagement and this reinforces their feeling that they can have an impact on their wider communities. Overall, the study suggests that involvement in collective rather than individual approaches to resolve problems is most likely to further increase individuals' levels community engagement.